2017
DOI: 10.1002/ente.201700061
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Multievaporator Adsorption Desalination Cycle for Gulf Cooperation Council Countries

Abstract: In Gulf Cooperation Council (GCC) countries, cogeneration‐based desalination processes consume almost 25 % of the total annual energy, and this number increases annually by 2.2 %. The high demand for fresh water can be attributed to the high gross domestic product growth rate, 24 %, and high water languishes, which are more than 10 %. Over the past two decades, GCC countries have spent tens of billions of dollars to expand their present and planned desalination capacities. It is foreseeable that with a busines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It was found that system recovery increased by about 25% compared to a single-stage RO system. Another type of hybrid system was studied in [112], presenting a mathematical model for a MED+RO and ADD system called MEDADRO, a hybrid thermal-membrane desalination configuration. A thermo-economic analysis was conducted, and it was found that the permeate water flow rate increased by 65.5%, and the price of producing water was reduced by 38.4% with respect to the basic configuration.…”
Section: Hybridization Of Add With Med and Swromentioning
confidence: 99%
“…It was found that system recovery increased by about 25% compared to a single-stage RO system. Another type of hybrid system was studied in [112], presenting a mathematical model for a MED+RO and ADD system called MEDADRO, a hybrid thermal-membrane desalination configuration. A thermo-economic analysis was conducted, and it was found that the permeate water flow rate increased by 65.5%, and the price of producing water was reduced by 38.4% with respect to the basic configuration.…”
Section: Hybridization Of Add With Med and Swromentioning
confidence: 99%
“…Recent hybridization trend of different desalination processes to overcome the individual processes limitations have ability to achieve SUPR ≈ 170 and energy efficiency up to 20% of TL [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], Kudus to the thermodynamic synergy between cycles. There is a need for more innovative processes that could maximize the input fuel exergy to boost water production, and it is plausible for process design to achieve up to 30% of TL, meeting the goals of sustainable seawater desalination.…”
Section: Standard Universal Performance Ratio (Supr)mentioning
confidence: 99%
“…They developed this correlation for pure water at saturation temperature ranges from 322 to 393 K. It can be noticed that there are two major gaps in available literature; firstly, no data is available for evaporation heat transfer for below 322 K and secondly, there is lack of data for salt solution as boiling point elevation changes with salt concentration. These two factors are important for processes industries falling film evaporators design as most of processes are performed below 322 K such as in food and desalination industries [30][31][32][33][34][35][36][37][38][39][40][41][42]. This was the main motivation of this study, to provide detailed parameters for falling film evaporators design for process industries.…”
Section: References Correlationmentioning
confidence: 99%